INNOVATION AND INVESTMENT PROJECTS: THE DIALECTIC OF THE INFLUENCE ON THE ECONOMIC SECURITY OF THE ENTERPRISE - VESHKIN, Yevhenii; KHUDIAKOV, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the article is to analyze the impact of the inclusion of innovation and investment projects in the enterprise's business strategy based on the study of risks and opportunities in the area of the implementation of the goal of strengthening economic security. The methodological basis of its achievement was a critical analysis of the scientific output of domestic researchers in the directions of determining the essence and components of the economic security of the enterprise, management of innovation-investment activities on a project basis, management of innovation-investment risks. The historical process of formation of the modern understanding of the category "economic security of the enterprise" and its interpretation in the scientific literature are revealed. The peculiarities of the implementation of the adaptation mechanism as a means of ensuring the sustainable functioning of the business entity in the conditions of challenges generated by the modern external environment have been studied. It is recognized that the management subsystem of innovation and investment activities is of key importance in achieving the goals of economic security of the enterprise. The stages of its implementation are disclosed and it is proved that the optimal principle of organizing the management of innovation and investment activity is the project principle, since the project activity is non-cyclical and does not have a permanent nature. The category "investment and innovation risk" was analyzed in terms of content and classification in the logical series "types of risks - types of risks - risk factors". The starting point of the typology was the criterion of the possibility of control by enterprises, which is key in the formation of the management architecture of innovation and investment projects. The dialectic of the influence on the economic security of the enterprise of the inclusion of innovation and investment projects in its business strategy is revealed, which consists in the following: they are both a threat and a guarantee of economic security. The direction of the impact of innovation and investment projects on the economic security of the enterprise depends on the adequacy of risk monitoring and the effectiveness of mechanisms for their neutralization or mitigation.
Keywords: innovations; innovation-investment projects; risks; opportunities; economic security of the enterprise; efficiency; business entities